The NASA archives : from Project Mercury to the Mars Rovers : 60 years in space - Bizony, Piers; Chaikin, Andrew, 1956-; Launius, Roger D.; Wiener, Nina (Editor) (Taschen, 2019)
To Infinity and Beyond Journey through the U.S. space program's fascinating pictorial history On October 1, 1958, the world's first civilian space agency opened for business as an emergency response to the Soviet Union's launch of Sputnik a year earlier. Within a decade, the National Aeronautics and Space Administration, universally known as NASA, had evolved from modest research teams experimenting with small converted rockets into one of the greatest technological and managerial enterprises ever known, capable of sending men to the moon.